Detection of Blood Protozoa Infecting Broiler Chicken Farms in Tanjung Gunung Village, District Jombang - Marchelia Arifiandani; Endang Suprihati; Wiwik Misaco Yuniarti; Nunuk Dyah Retno Lastuti; Poedji Hastutiek; Sunaryo Hadi Warsito (Journal of Parasite Science (JoPS), 2019)
Broiler chicken farms could be a part of potential source infection Leucocytozoonosis and Plasmodiosis disease due to the death of livestock. Broiler farms in Tanjung Gunung, District Jombang near the fields, water, and trees. This could be increase the population of vectors infection Leucocytozoonosis and Plasmodiosis. The main purpose of this researchis to detect Leucocytozoonosis and Plasmodiosis infections on broiler farms in Tnjung Gunung Village, District Jombang using 50 broiler chickens by Purposive Sampling  of 2 bredeers. The result show rhat there are 6 positive samples infected Leucocytozoonosis, while Plasmodiosis infection could not be fond. Need cage sanitation to break life cycles of vector Leucocytozoonosis and Plasmodiosis.